Discriminant and factorial validity of judo-specific tests in female athletes - Tavra, M.; Franchini, E.; Krstulovic, S. (Archives of Budo, 2016)
Background and Study Aim: To evaluate the state of preparedness of top athletes, specific tests are recommended as the specificity principle is paramount in competitive sports. The main objective of this study was the discriminant and factorial validity of four judo-specific tests in a sample of high-level junior female judokas.